2015
DOI: 10.3390/jmse3030981
|View full text |Cite
|
Sign up to set email alerts
|

The Tsunami Vulnerability Assessment of Urban Environments through Freely Available Datasets: The Case Study of Napoli City (Southern Italy)

Abstract: Abstract:The analysis of tsunami catalogues and of data published on the NOAA web site pointed out that in the Mediterranean basin, from 2000 B.C. to present, about 480 tsunamis occurred, of which at least a third involved the Italian peninsula. Within this framework, a GIS-aided procedure that takes advantage of spatial analysis to apply the Papathoma Tsunami Vulnerability Assessment model of urban environments is presented, with the main purpose of assessing the vulnerability of wide areas at spatial resolut… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
10
0
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(14 citation statements)
references
References 42 publications
1
10
0
1
Order By: Relevance
“…The maximum value is 3.49 m but most of the buildings were flooded less than 0.5 m. In general, both models show a spatial distribution with the highest RVI scores located closer to the shoreline and average to minor vulnerabilities in the inland buildings. Similar spatial patterns of the RVI scores have been described by different authors under different tsunami scenarios, geomorphologic settings and/or diverse urban features (e.g., Alberico et al, 2015;Dall'Osso et al, 2016). Dall'Osso et al (2016) showed that the Ex, Bv and Prot parameters are better distributed using the PTVA-4 model than with the PTVA-3 due to the difference in the re-scaling procedure adopted by the models.…”
Section: Ptva-3 Vs Ptva-4 Resultssupporting
confidence: 67%
See 1 more Smart Citation
“…The maximum value is 3.49 m but most of the buildings were flooded less than 0.5 m. In general, both models show a spatial distribution with the highest RVI scores located closer to the shoreline and average to minor vulnerabilities in the inland buildings. Similar spatial patterns of the RVI scores have been described by different authors under different tsunami scenarios, geomorphologic settings and/or diverse urban features (e.g., Alberico et al, 2015;Dall'Osso et al, 2016). Dall'Osso et al (2016) showed that the Ex, Bv and Prot parameters are better distributed using the PTVA-4 model than with the PTVA-3 due to the difference in the re-scaling procedure adopted by the models.…”
Section: Ptva-3 Vs Ptva-4 Resultssupporting
confidence: 67%
“…The first and second versions of the model were applied in the Gulf of Corinth, Greece (Papathoma and Dominey-Howes, 2003), and Seaside, Oregon, USA (Dominey-Howes et al, 2010), respectively. After improvements to the model, its third version was tested on the coast of New South Wales, Australia (Dall'Osso et al, 2009b), and has been widely used to assess the vulnerability of several coastal localities, such as the Aeolian Islands (Italy; Dall'Osso et al, 2010), Figueira da Foz (Portugal; Barros et al, 2013), Setúbal (Portugal; Santos et al, 2014), south of the Boso Peninsula (Japan; Voulgaris and Murayama, 2014), the southwest Atlantic coast of Spain (Abad et al, 2014), Naples (Italy; Alberico et al, 2015) and Chabahar Bay (Iran; Madani et al, 2016). Recently, a fourth version of the model has been tested at Botany Bay, Sydney (Australia; Dall'Osso et al, 2016).…”
Section: Vulnerability Modelmentioning
confidence: 99%
“…This methodology can also be applied to coastal areas characterized by high energy, causing overtopping and flooding during storms . The focus given to different components to assess the territorial vulnerability for areas with intense occupation, location of critical infrastructure, and environmental values allows the definition of prevention and mitigation measures …”
Section: Discussionmentioning
confidence: 99%
“…Risk is the probability of harmful consequences, or expected losses (deaths, injuries, property, livelihoods, economic activity disrupted or environment damaged) resulting from interactions between natural or human-induced hazards and vulnerable conditions [3][4][5][6][7][8]. Risk = Hazard Potential (H) x Vulnerability (V) [12].…”
Section: Gis and Risk Assessmentmentioning
confidence: 99%